Dual interfacial modification to improve the performance of CsPbBr3 perovskite solar cells. (April 2022) - Li, Xiaoyan; Yang, Meili; Hou, Shaochuan; Yan, Jiahao; Dong, Jingjing; Zou, Li; Xing, Jie; Liu, Hao; Hao, Huiying
Abstract: Although CsPbBr3 perovskite solar cells (PSCs) have excellent thermal and humidity stability, the narrow spectral absorption range and severe charge recombination within the CsPbBr3 film and device interfaces result in a low power conversion efficiency (PCE). In this work, self-synthesized graphene quantum dots (GQDs) and poly(3-hexylthiophene) (P3HT) are introduced to modify the m-TiO2 /CsPbBr3 and CsPbBr3 /carbon interfaces of CsPbBr3 PSCs, respectively. It is found that the carrier extraction and transfer are improved enormously after GQDs and P3HT dual modifications, which can be attributed to the passivated trap states, suppressed charge recombination, and reduced the interfacial energy barrier. Ultimately, for the carbon-based CsPbBr3 PSCs, a champion PCE as high as 9.74% with outstanding short-circuit current density (JSC ) of 9.36 mA cm -2 and open-circuit voltage (VOC ) of 1.42 V has been achieved, and the device stability has also been improved greatly. Such a strategy contributes to improving the performance of CsPbBr3 PSCs. Graphical abstract: Image 1 Highlights: GQDs and P3HT dual modifications were introduced to the carbon-based CsPbBr3 PSCs. GQDs were prepared by a solvothermal method, and applied in TiO2 /CsPbBr3 interface. P3HT was introduced to modify the CsPbBr3 /carbon interface. Carrier extraction and transfer were improved enormously after dual modifications. After dual modifications, for CsPbBr3 PSCs, a champion PCE of 9.74% was achieved.